2014
DOI: 10.4322/rbcv.2014.018
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic evaluation of hG-CSF transgenic goat conceptus

Abstract: The objective of this study was to evaluate the development of transgenic (T) goat embryos and fetuses for human Granulocyte Colony Stimulating Factor (hG-CSF) by ultrasonography. Four pregnancies in non-transgenic (NT) goats were obtained after fertilization (either fixed-time artificial insemination or natural mating) using the T male for hG-CSF. Ultrasound examinations were carried out at 30, 40 (transrectal via), 50, 60, 90 and 120 days of pregnancy (transabdominal via). Some parameters were observed such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…Amer (2010Amer ( , 2008 used ultrasound to measure crown-rump lengths and biparietal diameters in pregnant goats and found similar values at 45 days of pregnancy. Oliveira et al (2014), on evaluating the embryonic and fetal development in Canindé goats, found values similar to our study in terms of the diameter of the embryonic vesicle and the crown-rump length for the same period of gestation. At parturition, fecundity was statistically similar (P > 0.05) between the groups, with an overall mean of 1.39 ± 0.11 kids, and there were no differences in the multiple birth rate between groups.…”
Section: Resultssupporting
confidence: 67%
“…Amer (2010Amer ( , 2008 used ultrasound to measure crown-rump lengths and biparietal diameters in pregnant goats and found similar values at 45 days of pregnancy. Oliveira et al (2014), on evaluating the embryonic and fetal development in Canindé goats, found values similar to our study in terms of the diameter of the embryonic vesicle and the crown-rump length for the same period of gestation. At parturition, fecundity was statistically similar (P > 0.05) between the groups, with an overall mean of 1.39 ± 0.11 kids, and there were no differences in the multiple birth rate between groups.…”
Section: Resultssupporting
confidence: 67%
“…Another importance of the determination of the age of pregnancy is to predict the delivery time to avoid problems that occur during the parturition and thus reduce the fetal loss due to dystocia (2). The age of pregnancy in farm animals is estimated depending on the time of insemination, which is considered the zero-day of pregnancy (3). This method is more accurate than other methods to determine the age of the pregnancy.…”
Section: Introductionmentioning
confidence: 99%